1999
DOI: 10.1016/s0022-328x(98)01068-7
|View full text |Cite
|
Sign up to set email alerts
|

Titanium σ-acetylides as building blocks for heterobimetallic transition metal complexes: synthesis and redox behaviour of π-conjugated organometallic systems

Abstract: A series of related Ti s-acetylides of the type {Ti}C CR ({Ti}= (h 5 -C 5 H 5 ) 2 Ti(CH 2 SiMe 3 ); 2: R=SiMe 3 ; 3: R= C 6 H 3 (CH 2 NMe 2 ) 2 -3,5; 4: R= C 6 H 2 I-4-(CH 2 NMe 2 ) 2 -3,5; 5: R=C 6 H 4 CN-4; 6: R= C 5 H 4 N-4; 7: R=Fc, Fc= (h 5 -C 5 H 4 )Fe(h 5 -C 5 H 5 ); 8: R=C 6 H 4 (C C{Ti})-4) have been prepared by reacting the corresponding lithium acetylides with {Ti}Cl (1). The X-ray crystal structure determination of {Ti}C CSiMe 3 ( 2) is reported. This compound exhibits a one-dimensional (1D) arrang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 95 publications
1
18
1
Order By: Relevance
“…This potential is similar to that found in {Ti}(C"C-C 5 H 4 N-[Ru]) ({Ti} = (g 5 -C 5 H 5 ) 2 Ti(CH 2 SiMe 3 )). In comparison with [Ru]-NC 5 H 5 , the ruthenium oxidation potential of 12 is shifted to a more negative value indicating that the oxidation is facilitated by the presence of a platinum building block in para-position [21]. Measuring the cyclic voltammograms upto 1.6 V results in the appearance of an additional irreversible oxidation wave at E p,ox = 1.27 V (Fig.…”
Section: Cyclic Voltammetrymentioning
confidence: 96%
“…This potential is similar to that found in {Ti}(C"C-C 5 H 4 N-[Ru]) ({Ti} = (g 5 -C 5 H 5 ) 2 Ti(CH 2 SiMe 3 )). In comparison with [Ru]-NC 5 H 5 , the ruthenium oxidation potential of 12 is shifted to a more negative value indicating that the oxidation is facilitated by the presence of a platinum building block in para-position [21]. Measuring the cyclic voltammograms upto 1.6 V results in the appearance of an additional irreversible oxidation wave at E p,ox = 1.27 V (Fig.…”
Section: Cyclic Voltammetrymentioning
confidence: 96%
“…Exchange of one methyl group by a [Ti]Cl unit (9, n = 1) shifts the oxidation potential by 0.37 V to more negative values. A second replacement (14, n = 2) leads to a further shift of 0.25 V. The magnitude of the shift is very notable since, for example, in (g 5 -C 5 H 5 ) 2 Ti(CH 2 SiMe 3 )(C"CFc) the ferrocene oxidation is only facilitated by 0.080 V as compared to HC"CFc [29]. Therefore, it can be concluded that in 9, 14 and 15 an effective resonance stabilization of the oxidized species (radical cation) takes place.…”
Section: Cyclic Voltammetrymentioning
confidence: 99%
“…13 C{ 1 H} NMR (CDCl 3 ): [d] À0.3 (SiMe 3 ), 111.5 (C 2 H/ C 6 H 4 ), 114.0 (C 6 H/C 6 H 4 ), 115.0 (CH/C 5 H 4 ), 119.1 (CH/C 5 H 4 ), 123.8 (C 4 H/C 6 H 4 ), 127.2 (CH/C 5 H 4 ), 128.9 (CH/C 5 H 4 ), 129.4 ( i C/C 5 H 4 ), 130.4 (C 5 H/C 6 H 4 ), 149.0 ( i C 3 H/C 6 H 4 ), 170.2 (C-OTi). 29 [Ti](OC 6 H 4 -4-NO 2 ) 2 (13)…”
Section: Synthesis Ofmentioning
confidence: 99%
“…Triazacycloundecane derivatives are, in general, less stable than the triazacyclononane-based complexes and this characteristic prevents their study by cyclic voltammetry. The stability of the cations is higher than that of the reduced metal complexes and thus [Ti{N 3 [9] [16][17][18] On the other hand, the value of -1.58 mV measured for E 1/2 red of 7 reflects the additional stability of the LUMO when C 6 H 5 is replaced by o-C 6 H 4 F. The similarity between the reduction potential of 7 and that of [Ti{O 3 [9]-N 3 }PF 6 (H 3 O 3 [9]N 3 = 1,4,7-tris(5-tert-butyl-2-hydroxybenzyl)-1,4,7-triazacyclononane; E 1/2 red = -1.52 mV) shows that the donor ability of the amide moieties in 7 is comparable to that of the alkoxide fragments in [Ti{O 3 [9]N 3 }]PF 6 . [17] The voltammograms of 7 and 9 display addition redox peaks at -0.22 V and -0.20 V, respectively, that are due to the I -counterion.…”
mentioning
confidence: 99%